A Concise History of Christianity - Peterson, R. Dean (Belmont, Calif. Wadsworth Publishing Company, 1993)
A CONCISE HISTORY OF CHRISTIANITY is a brief and chronologically organized overview of the Christian religious tradition that acquaints students with the history of the Christian Church, describing the people, places, and ideas that have shaped Christiani
Keywords: Church history